Pustular reaction in adult-onset immunodeficiency due to anti-interferon-gamma autoantibodies - Julanon, Narachai; Danpanichkul, Pojsakorn; Choonhakarn, Charoen; Chaowattanapanit, Suteeraporn; Anunnatsiri, Siriluck; Chetchotisakd, Ploenchan; Kiratikanon, Salin; Rujiwetpongstorn, Rujira; Tovanabutra, Napatra; Chiewchanvit, Siri; Chaiwarith, Romanee; Phinyo, Phichayut; et al. (Frontiers in Immunology, 2025)
IntroductionCutaneous manifestations in adult-onset immunodeficiency (AOID) resulting from anti-interferon-gamma autoantibody (AIGA) are prevalent and can be classified into infective and reactive disorders. To date, no clinical studies have specifically examined pustular reaction in patients with AOID. This study aimed to provide an original characterization of the clinical manifestations associated with pustular reaction in AOID and to compare these features with those observed in a clinically similar entity, generalized pustular psoriasis (GPP).MethodsA retrospective study was conducted between January 2014 and June 2023 at the dermatology clinics of Maharaj Nakorn Chiang Mai Hospital, Chiang Mai and Srinagarind Hospital, Khon Kaen, Thailand. The study included adult patients diagnosed with AOID presenting with pustular reaction, defined as pinhead-sized pustules on an erythematous base occurring any area of skin, as well as those diagnosed with GPP. Cases with pustular drug eruption and with non-sterile pustules were excluded. Data analysis was performed using both univariable and multivariable statistical methods.ResultsTotal of 64 patients diagnosed with AOID who subsequently developed a pustular reaction were included in the study. Clinically, the cutaneous manifestations were characterized by discrete, pinhead-sized pustules distributed on erythematous bases, predominantly affecting the trunk and extremities. A concomitant infection was identified in 54 patients (84.4%). Rapid-growing mycobacteria represented the most frequently identified pathogens, with lymph nodes being the most commonly involved anatomical site. Comparative analysis with a cohort of 77 patients diagnosed with GPP elucidated distinct clinical hallmarks differentiating the two entities. Lymphadenopathy, hepatomegaly, and splenomegaly emerged as distinguishing features more frequently associated with AOID-related pustular reaction. In contrast, the presence of geographic tongue and nail involvement was more characteristic of GPP. In instances where these pathognomonic features were absent, a multivariable predictive model was developed to aid in diagnostic differentiation. This model incorporated the presence of concomitant infections, elevated serum globulin levels, and increased alkaline phosphatase levels.ConclusionAmong patients presenting with sterile pustular eruptions, the presence of lymphadenopathy, hepatomegaly, and splenomegaly served as perfect clinical predictors of an underlying pustular reaction associated with AOID. In cases where these hallmark features were absent, a predictive algorithm incorporating the presence of a concomitant infections, serum globulin concentration, and alkaline phosphatase level demonstrated robust utility in estimating the likelihood of AOID-associated pustular reaction.